Isolation and characterisation of Polylactic acid-degrading actinobacteria / Lim Peek Eek - Lim, Peek Eek (2013)
Polylactic acid (PLA) is one of the biodegradable plastics available in the market where the monomers lactic acids are joined together by ester bonds. Actinobacteria is a bacterial group with high G+C mol% and capability to produce various kinds of useful secondary substrates due to their unique metabolic pathways. In this study, soil samples from a contaminated landfill site and a non-contaminated soil at camp site were collected and screened for actinobacteria that have the ability to degrade PLA. PLA-emulsified medium, which contains only PLA as carbon source, was used as selective isolation medium to isolate PLA degraders from soil samples. Isolated strains were characterized by using polyphasic method. A total of 235 strains of PLA degrading actinobacteria were isolated from ten soil samples. Among these 235 strains, PLA degraders were found from different genera such as Agromyces, Rhodococcus, Micromonospora, Mycobacterium and Streptomyces, contrary to previous reports. In addition, two novel strains, which are members of Agromyces and Mycobacterium, were identified. Relative enzyme activity of isolated strains was checked and most of the strains have relative enzyme activity from 1.00 to 3.00 toward both low and high molecular weight PLA. Crude enzyme was extracted from strains P253 and P256, which had a relative enzyme activity higher than 3.00 for both low and high molecular weight PLA. Molecular weight of PLA-degrading enzyme was determined by using SDS PAGE and zymography method. The PLA-degrading enzyme from strains P253 and P256 were found to have molecular weight ranging from 10-35kDa and 35-40kDa, respectively.